Phytochemical study on Berberis sibirica Pall. - A Solongo; R Istatkova; S Philipov; S Javzan; D Selenge (Mongolian Journal of Chemistry, 2014)
From the aerial parts (700g) of berberis sibirica pall. 6 isoquinoline alkaloids of protoberberine, protopine, benzophenantridine and proaporphine type were isolated. The known alkaloids (-)-tetrahydropseudocoptisine, pseudoprotopine, (+)-chelidonine and (+)-glaziovine are new for the family berberidaceae. from the aerial part ii (3.9 kg) 14 isoquinoline alkaloids of aporphine, proaporphine, protoberberine, protopine, benzylisoquinoline, bisbenzylisoquinoline, proaporphine-benzylisoquinoline and simple isoquinolin type were isolated and identified. The aporphine alkaloid 1-o-methylisotebaidine and simple isoquinoline dehydrocorypalline have been found for the first time in the family of berberidaceae. From the roots of b. sibirica 10 isoquinoline alkaloids of protoberberine, benzylisoquinoline, bisbenzylisoquinoline, aporphine-benzylisoquinoline and proaporphine-benzylisoquinoline type were isolated. 1,10-di-omethylpakistanine has been reported for the first time as a natural alkaloid. The known alkaloids (-) -isothalidezine and (+)-armepavine have been found for the first time in the family berberidaceae. All structures were determined by physical and spectral data. DOI: http://dx.doi.org/10.5564/mjc.v12i0.185 Mongolian Journal of Chemistry Vol.12 2011: 117-122